Developing a wireless based dynamic management mechanism for intravenous drip scheduling. (2015) - Chen, Chien-Liang; Hsieh, Nan-Chen; Hung, Lun-Ping
In this rapidly developing high-tech environment, building a nursing information system is essential. When an emergency occurs, nurses must immediately remove obstacle interrupting medical care to assist medical treatment successfully. In this paper, a system built in a mobile nursing station accompanied by a high-tech device installed in the infusion drip equipment transmitting signals through a ZigBee wireless network is proposed. This system uses a dynamic wireless infusion monitoring mechanism. When an emergency occurs, the intravenous drip sends out an alert message through the wireless environment to the system in the mobile nursing station. The system will reschedule previous processing ranks to assist nurses in taking care of routine medical operations efficiently. By applying this system, nurses can devote themselves to providing better quality medical care and claims for medical negligence or medical malpractice can be reduced.